2009
DOI: 10.1038/tpj.2009.21
|View full text |Cite|
|
Sign up to set email alerts
|

Association of genotypes of the CYP3A cluster with midazolam disposition in vivo

Abstract: The genes that encode for CYP3A4 and CYP3A5 are located in the same region (CYP3A cluster) on chromosome 7. Midazolam (MDZ) is a substrate for both CYP3A4 and CYP3A5. We hypothesize that MDZ disposition in vivo is associated with genotypes of the CYP3A cluster. A meta-analysis of the pharmacokinetic (PK) parameters from seven clinical trials was carried out, in which MDZ was administered both intravenously and orally. DNA samples were available from 116 patients. There were significant ethnic differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 49 publications
10
43
0
Order By: Relevance
“…Miao et al (2009) concluded that women exhibited 19% higher weight-corrected systemic clearance and 38% higher oral clearance than men (P Ͻ 0.05). This study reviewed the data from seven clinical studies, which were previously conducted by their research team, but only included subjects whose DNA samples were available.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Miao et al (2009) concluded that women exhibited 19% higher weight-corrected systemic clearance and 38% higher oral clearance than men (P Ͻ 0.05). This study reviewed the data from seven clinical studies, which were previously conducted by their research team, but only included subjects whose DNA samples were available.…”
Section: Introductionmentioning
confidence: 99%
“…The oral clearance data of this study were surprisingly higher than those of other included studies. As a result, the retrospective study by Miao et al (2009) is at a higher risk of bias compared with that for a prospective study. In the other retrospective study, Chen et al (2006b) found that women exhibited 11% higher mean weight-corrected MDZ systemic clearance and 28% higher oral clearance than men (P Յ 0.01).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacogenetic studies show that genetic variations in this gene and other genes of CYP450 superfamily (specially polymorphism) can affect metabolism process of drugs [1]. Peer review studies about CYP3A4*1B have shown different frequency of variant allele in population with different ethnic background [17], [18], [19], [15], [14], [20], [15`]. We showed 3% allele frequency for variant allele in studied population as one of local country in Asian population.…”
Section: Methodsmentioning
confidence: 59%